Creep Behavior of Fe–25Ni–15Cr‐Based Alumina‐Forming Austenitic Steel. Issue 2 (17th October 2022) - Sun, Gang; Sun, Hongying; Wang, Man; Zhou, Zhangjian
Abstract : The creep behavior of Fe–25Ni– 15Cr‐based aluminum‐forming austenitic stainless steel is investigated at 700 °C, under the selected stress of 100, 140, 170, and 180 MPa, respectively. Creep properties are analyzed in terms of stress exponent ( n ) and creep damage tolerance factor ( λ ). Within the tested stress range, there is an order of magnitude difference between the minimum creep rate and steady creep rate. The evolution of the microstructures after creep test with the stresses of 140, 170, and 180 MPa is characterized by scanning electron microscopy and electron backscatter diffraction detectors, respectively. With the decreased creep stress, the creep void size shows an increasing trend. Higher stress would accelerate the process of recrystallization during the creep process at 700 °C. The proportion of high‐angle grain boundaries increases to a certain extent under high‐stress conditions. A large amount of Laves and NiAl phases are observed after creep test at 140, 170, and 180 MPa, respectively. Abstract : Creep behavior of Fe–25Ni–15Cr‐based aluminum‐forming austenitic stainless steel is investigated at 700 °C, under the selected stress of 100, 140, 170, and 180 MPa, respectively. A large amount of Laves and NiAl phases are observed after creep test. Higher stress will accelerate the process of recrystallization during the creep, which accelerates creep fracture.